KEDUDUKAN DPRD KABUPATEN JEMBRANA DALAM PENGAWASAN TERHADAP PENGELOLAAN KEUANGAN DAERAH - Karismawati, Ni Putu Wilda; Yusa, I Gede; Suarbha, I Wayan (Kertha Wicara : Journal Ilmu Hukum; Vol 1 No 01 (2012))
AbstractParliament is element of the regional administration, the council has three functions,legislative, budgetary, and oversight. oversight function is not described in theoversight of the financial management area, so this area of financial managementoversight becomes blurred if being on legislation or oversight function.
Keywords: Oversight, Parliament, Management, Financial local